A New Species of Afrotropical Ants in the Genus Bothroponera (Hymenoptera: Formicidae: Ponerinae) - Abdulmeneem M. A. Joma; William P. Mackay (Psyche: A Journal of Entomology)
We describe a new species of Afrotropical Bothroponera from Whittlesea City, Eastern Cape Province, South Africa. This species is unique among the African Bothroponera as it is the only species with a horizontal propodeal spiracle. It is also the largest species of African Bothroponera (total length 14.80–15.65). The clypeus lacks a medial longitudinal carina, the head is subquadrate, the sculpture is mostly foveolate, and the second gastral segment nearly lacks sculpturing. We compare the new species to the similar B. cavernosa and B. cavernosa var. montivaga. We also compare the new species to all of the other 10 taxa that belong to the cavernosa complex. A key to the cavernosa complex species of the Afrotropical Bothroponera is provided along with diagnosis, comparison, distribution, habitat, biology, and etymology for the new species.